Pars plana vitrectomy for vitreoretinal interface disorders coincident with intermediate stage age-related macular degeneration - Tarkova, Anna; Hejsek, Libor; Jurecka, Tomas; Wolkova, Petra; Rubesova, Martina; Hackl, Michal (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2023)
BACKGROUND AND AIMS: Currently around 67 million people in Europe are affected by some form of age-related macular degeneration (AMD). As most known types of vitreoretinal (VR) interface disorders can coexist with AMD and as we can favourably affect the former with vitreoretinal surgery, our goal was to evaluate the results of vitreoretinal interface disorder surgery with macular peeling in relation to coincident intermediate stage AMD. METHODOLOGY: This was a retrospective evaluation of eyes operated with 25-gauge pars plana vitrectomy (PPV). The monitored parameters were anatomical and functional findings and, safety of the procedure. The surface of the macula was stained with trypan blue and treated (peeling) with a disposable microforceps. 10% perfluoropropane, or the air tamponade was used. Distance visual acuity was examined on the ETDRS chart, the macular finding was monitored by OCT and photodocumented. The post-operative face-down position was 3-5 days. The follow-up period was 6 months. RESULTS: 17 eyes (14 patients, woman 86%) mean age 74 years. The primary indications for the procedure were: idiopathic macular hole (IMD) 59%, epiretinal membrane 29% and vitreomacular traction syndrome 12%. Ophthalmoscopic and OCT findings of intermediate dry form of AMD (100%), in 24% was drusoid ablation of the pigment leaf. In all cases of IMD, primary closure occurred. Input visual acuity 0.1-0.6 improved to 0.2-0.9 at the end of the follow-up period (P<0.05). No complications during surgery or progression of AMD in the follow-up period were observed. CONCLUSION: PPV for vitreoretinal interface disorders have similar anatomical results, whether the outer part of the retina is disrupted by intermediate AMD or not. Functional results are affected by possible disruption of the RPE or the outer layers of the neuroretina by AMD. The PPV procedure has a standard security profile. It is safe and does not affect the progression of AMD in the short term.
Keywords: pars plana vitrectomy; nemoci retiny; Humans; Retinal Diseases; Female; Aged; optická koherentní tomografie; Macular Degeneration; senioři; lidé; oční nemoci; vitreoretinal interface; aged-related macular degeneration; Vitrectomy; makulární degenerace; ženské pohlaví; Retrospective Studies; Retinal Perforations; perforace sítnice; epiretinální membrána; retrospektivní studie; Tomography, Optical Coherence; Eye Diseases; vitrektomie; visual acuity; Epiretinal Membrane